Good-Practice Note : Governance and Anti-Corruption Innovations in the Da Nang Priority Infrastructure Investment Project, Vietnam - Golan, Amnon (World Bank, Washington, DC, 2012)
As Vietnam's fourth largest urban area, Da Nang is expected to grow exponentially in the next two decades. The Da Nang priority infrastructure investment project which operates in a challenging governance environment has introduced a number of innovative Governance and Anti-Corruption (GAC) interventions through a Governance and Transparency Action Plan (GTAP). The key features and challenges of the project GTAP assessed along three dimensions governance and political economy, fraud and corruption risks in procurement and financial management, and demand side governance (transparency, participation and third party monitoring) are discussed in this learning note.